One-dimensional River Network Hydrodynamic Model Based on HLL Finite Volume Method: A Case Study of Jiaokou–Yinjiang Region - GU Weiwei; CHEN Longzan; ZHANG Jingsi; LI Weizheng; YANG Yanfei; ZHANG Weiguo (Renmin Zhujiang)
To address one-dimensional river network models' difficult solution in complex areas and insufficient capability of capturing shock waves, this paper develops a hydrodynamic model suitable for complex river networks in mountainous and plain areas. The model is based on the finite volume discretization of the Saint-Venant equations and adopts the HyperLogLog (HLL) approximate Riemann solver to solve numerical fluxes at interfaces. Additionally, an extended Riemann method is employed to solve the water levels at bifurcation points. The model's validity is confirmed by a dam-break model, demonstrating strong capabilities for handling cross-critical flow changes. Meanwhile, the model features stable calculation with accurate results even under dry-bed situations. Thus, the model is further applied to the Jiaokou–Yinjiang Region and the results show that it effectively tackles the dry-bed problems encountered during low inflows in mountainous areas. Additionally, during floods, this model exhibits high simulation accuracy, accurately reflecting the flood rise and recession processes as well as the timing of flood peaks. Compared to the finite difference method, the model features comparable simulation accuracy and computational efficiency, with its computational efficiency improved by 15.7%. In terms of early warning and forecasting of water levels, the proposed model has higher accuracy and can provide significant support for flood control decision-making. The built model can provide new insights for flood forecasting and simulation in mountainous areas and other complex terrains.